2013
DOI: 10.1186/1465-9921-14-47
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion molecules in subjects with COPD and healthy non-smokers: a cross sectional parallel group study

Abstract: BackgroundThe aim of the study was to investigate how the expression of adhesion molecules changes as neutrophils migrate from the circulation to the lung and if these changes differ between non-smoking subjects and smokers with and without COPD.MethodsNon-smoking healthy subjects (n=22), smokers without (n=21) and with COPD (n=18) were included. Neutrophils from peripheral blood, sputum and bronchial biopsies were analysed for cell surface expression of adhesion molecules (CD11b, CD62L, CD162). Serum, sputum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 37 publications
2
20
0
5
Order By: Relevance
“…These findings are consistent with small studies showing that circulating sICAM-1 is increased in patients with COPD (11, 12). The result for sE-selectin was of similar magnitude to sICAM-1 in minimally adjusted analyses, but was non-significant, in part due to the smaller sample size, and was further attenuated after full adjustment.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are consistent with small studies showing that circulating sICAM-1 is increased in patients with COPD (11, 12). The result for sE-selectin was of similar magnitude to sICAM-1 in minimally adjusted analyses, but was non-significant, in part due to the smaller sample size, and was further attenuated after full adjustment.…”
Section: Discussionsupporting
confidence: 93%
“…ICAM-1 blocking antibodies reduce neutrophilic pulmonary inflammation by two-thirds in animals, suggesting that ICAM-1 may be critical in neutrophil access to the lung (10). Small studies have found altered ICAM-1 and E-selectin in COPD (11, 12), and cross-sectional studies have found inverse associations between soluble ICAM-1 (sICAM-1) and lung function (13, 14). However, no longitudinal study has assessed the relationship between ICAM-1 or E-selectin and the progression of emphysema or decline in lung function.…”
Section: Introductionmentioning
confidence: 99%
“…В ряде исследований показано, что увеличение плазменных растворимых молекул межклеточной адгезии ICAM 1 оказывает повреждающее действие на эндотелий [20]. K.Blidberg et al установлено, что уровни растворимого ICAM 1, ICAM 3 в сыворотке увеличивается при ХОБЛ, что подтверждает систем ную воспалительную активность [5].…”
Section: Discussionunclassified
“…Согласно резуль татам многочисленных исследований, у больных ХОБЛ отмечаются изменения структуры и актива ция одних из основных эффекторных клеток -нейт рофилов периферической крови [3]. У больных ХОБЛ нейтрофилами секретируются сериновые про теазы, включая нейтрофильную эластазу, катепсин G и протеиназу 3, которые приводят к деструкции аль веолярной стенки, обладают повышенной хемотак сической реакцией и экспрессией поверхностных клеточных адгезивных молекул [4], что свидетель ствует о системной воспалительной активности [5].…”
Section: оригинальные исследованияunclassified
“…Эта молекула экспрессируется клетками крови (тромбоцитами, нейтрофилами, моноцитами, лимфоцитами) и эндо телиальными клетками. Концентрация растворимой формы PECAM 1 в сыворотке крови курящих паци ентов с ХОБЛ выше, чем у курящих здоровых лю дей [48]. Кроме того, у курящих пациентов с ХОБЛ повышено количество циркулирующих в крови эн дотелиальных микрочастиц, содержащих PECAM 1, по сравнению с курящими здоровыми людьми.…”
Section: ингибиторы Pecamunclassified